MEKANISME DAN KINERJA PADA SISTEM PERONTOKAN PADI - Heny Herawati (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2008)
Efficiency is the main factor which contributes in choosing the type, system and tool supporting paddy post harvesting. One step of post harvest process is paddy threshing. Inefficiency in paddy threshing caused 5% losses. Factors which contribute in capacity and the work of paddy thrasher are paddy variety, post harvest system, threshing mechanism, delay threshing and harvest lost factor. Actually, paddy threshing system divided into three categories such as traditional threshing with gebot, pedal thresher and power thresher machine. Further study in paddy threshing is needed to know about mechanism, the work and the factors which influence threshing.